The development of a front office hotel information system for White Rock Beach Resort - Canto, Emilio Joaquin Zamora (Animo Repository, 2006)
White Rock Beach Resort is a property along the coastline of Subic Bay, Zambales that has a total of 130 hotel rooms. It has an office in Libis, Quezon City specifically for sales, marketing, and accounting activities. As both the Subic and Libis offices receive inquiries and reservations from patrons and travel agencies, the availability of the 130 hotel rooms has to be managed by the two offices. Due to the lack of a centralized file for booked reservations and checked-in guests, this process has resulted in excessive and costly phone calls between the two offices especially during long weekends and peak vacation seasons. In addition, due to policies on cancelled reservations with down payments and the high number of reservation forms produced, revised, and cancelled each during these periods, tracking cancelled reservations that are still valid is difficult because of the possibility of misplacing reservation forms. In the Subic office, the accuracy of a guests bill is a problem for about 10% of all bills produced. There are cases wherein guests are charged an amount that is less than or greater than the correct amount. Moreover, it takes up to 15 minutes upon check-out to produce the bill because the total amount still has to be computed, making guests wait in the meantime. Lastly, although the hotel is able to collect a lot of useful data about its guests, this data is kept filed and left unused. This study designed, implemented, and evaluated a Hotel Information System (HIS) that supports the front office operations of White Rock Beach Resort. The HIS is composed of a total of nine programs, each designed to be used by a certain type of user. To solve the problems encountered by the hotel in its front office operations, the combined features of the HIS: 1) Enable users to determine the available rooms on a certain range of dates based on real-time data from booked reservations and existing check-ins 2) Provide screens to create, modify, cancel, and view hotel reservations 3) Provide screens to encode guest check-in data, which includes personal information, arrival and departure, room numbers, and room rates 4) Provide point-of-sales programs to encode charges that are included in guests bills 5) Produce reports from data collected by one program or the entire system. To verify and validate the design, the HIS was subjected to unit, integration, system, and user acceptance tests. An overall mean score of 4.56 out of 5.00 in the user acceptance tests confirms that the HIS meets the requirements of the end users within the scope set by the proponent and satisfies the study's evaluation criteria. The methodology used in this study, the Rational Unified Process (RUP), provided a disciplined approach to the development process. The UML artifacts created and updated during each phase aided most of the development activities including design and specification, coding, and testing. This was possible mostly because the study used Microsoft C# .NET, which is an object oriented programming language, as the development tool. Because of the iterative nature of the RUP, the proponent built the HIS in pieces beginning with the most critical functionalities. With this, the stakeholders were able to periodically see the partially completed system and provide inputs as needed. This process reduced potential rework on the part of the proponent and showed the stakeholders that there is progress. Based on the results achieved and the qualities of the methodology, the proponent concludes that the RUP is an applicable methodology for developing hotel information systems.